Micro‐Supercapacitors: 3D‐Printed Stretchable Micro‐Supercapacitor with Remarkable Areal Performance (Adv. Energy Mater. 14/2020). Issue 14 (14th April 2020) - Li, Xiran; Li, Hongpeng; Fan, Xiangqian; Shi, Xinlei; Liang, Jiajie
Abstract : In article number 1903794, Jiajie Liang and co‐workers present a strategy for the 3D‐printing and unidirectional freezing of a nanocomposite gel composed of MXene, MnO2 nanowires (NWs), AgNWs, and C60 to construct intrinsically stretchable micro‐supercapacitors (MSCs) with thick and honeycomb‐like porous interdigitated electrodes. The 3D‐printed MSC exhibits high areal capacitance of 216.2 mF cm −2 at 10 mV s −1, and remains stable when stretched up to 50%.